Behavior of Osteoblastic Lineage Cells When in the Presence of Tamoxifen: In Vitro and In Vivo Studies on Osseointegration - Fiorin, Luiz Guilherme [UNESP]; Galliera, Emanuela; Matheus, Henrique R. [UNESP]; Henin, Dolaji; Ervolino, Edilson [UNESP]; Simionato, Gabriela Carrara [UNESP]; Almeida, Juliano Milanezi de [UNESP]; Dellavia, Claudia (MDPI, 2025)
Background/Objectives: Tamoxifen, a selective estrogen receptor modulator widely used as an adjunct in the treatment of breast cancer, has known effects on bone metabolism, although its impact on osseointegration and cellular responses during early bone healing remains unclear. Understanding these effects is essential given the increasing use of dental implants in cancer survivors. The study aimed to observe the influence of tamoxifen on human osteosarcoma (SAOS-2) cells lines, as well on the osseointegration of titanium implants in ovariectomized female rats. Methods: SAOS-2 cells were incubated with Dulbecco's modified growth medium. Six titanium (Ti) disks were used at each time point. The samples were divided into groups with the presence (TAM, n = 36) or not (CTR, n = 36) of tamoxifen in a concentration of 2 μM. In vivo, 72 animals were divided in groups with bilateral ovariectomy or SHAM and tamoxifen administration or not (15 mg/kg). Cell viability, mineralization rate, and collagen synthesis were assessed, as well as bone/implant contact (BIC) and bone ingrowth (BIN). Results: Tamoxifen caused a decrease in SAOS-2 viability, although an increase in the mineralization rate was observed. In vivo, the TAM groups presented higher BIC and BIN when compared to their control, but a lower percentage of mature collagen cells. Conclusions: Based on our findings, in vitro, the therapy with TAM slightly reduced the viability of SAOS-2 cells while significantly increasing the mineralization rate. In vivo, the therapy positively influenced BIC and BIN during the osseointegration phase.